CONSTRUCTIVISM LEARNING IN WRITING OF LITERARY WORKS - Taufik, Muhammad; Yusuf, Marwah Juwita; Rijal, Andi Samsul (Elite : English and Literature Journal, 2020)
Constructivism is a function as a method in learning both science and socio-cultural sciences, including literary learning. The purpose of this research was to find out the Increasing of student’s performance in writing literary works and to know the effectiveness of constructivist methods in the teaching of writing literary works. This study was experimental method. There were 30 samples in this study, and the assessment was through tests and non-tests. The post-test showed a higher difference than the pre-test, that was 18%. So the constructivism method can be used in the teaching of writing literary works and able to improve student writing competence. The method of constructivism helps students to organize creative ideas in writing literary works. Students can develop ideas, characterizations, good storylines and the ability to raise current phenomena in writing stories.